Efeitos dos fármacos alfa-adrenérgicos na eletroejaculação de catetos (Tayassu tajacu) - Paiva, Ariana Lopes Correia de (2012)
The objective was to verify the existence of potential associations between medetomidine and atipemazole in electroejaculation of peccaries anesthetized with propofol. The twelve peccary received the following treatments: control, none pre medication; medetomidine 40 microg.Kg-1 IV or atipemazole 200 microg.Kg-1 IV. All animals received 5 mg.Kg-1 IV propofol induction and maintenance of anesthesia. Were evaluated: heart rate, respiratory rate, systolic, diastolic, and mean blood pressure, temperature, blood gas and cortisol. For the semen evaluated the onset time of ejaculation, erection, and seminal variables. We analyzed the data by one way ANOVA for repeated measures followed by Tukey. P < 0.05 were considered significant. For semen, we obtained only a significant difference in sperm concentration between atipemazole (100.00 ± 25.96 x 106) and medetomidine (220.20 ± 49.74 x 106), yet both did not differ from controls (180.00 ± 50.71 x 106). Medetomidine promoted cardiovascular changes more significant. There was no significant difference in cortisol levels between the treatments compared. Atipamezole and medetomidine do not increase the peccary s erectile function. However, they influence the concentration of sperm and ejaculatory function in the peccary undergoing electroejaculation. Propofol alone, resulted in a more efficient anesthesia for peccary collection semen